PENERAPAN METODE THE LEARNING CELL BERBANTU MEDIA POP-UP STORY BOOK UNTUK MENINGKATKAN HASIL BELAJAR IPS KELAS V SDN CANDI 01 SEMARANG - Wahyu Dwi Martiningdyah (ELEMENTARY SCHOOL JOURNAL PGSD FIP UNIMED, 2017)
ABSTRACTThis study aims to improve the learning outcomes of IPS with the application of the method of learning cell learning media pop-up story booksiswa class V SD Negeri Candi 01 Semarang. The research method is quantitative with Pre-Experimental Design type one group pretest-postest design. The subjects were 24 students. Data analysis techniques used are qualitative description and quantitative description. The result of the research shows that there is an increase of IPS learning result through thelearning cell method using pop-up story book media in class V students. Based on field observation, the average of students' learning outcomes before treatment is ≤ 50%, and the expected result after treatment is ≥ 75% .Keywords: The Learning Cell, Learning Outcomes, Pop-Up Story Book